Evaluasi Psikometri Sebagai Pencegahan Penyalahgunaan Senjata Api Oleh Anggota Polri: Studi di Propam Polrestabes Palembang - Tiara Wulandari (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The misuse of firearms by police officers is a serious concern that can endanger public safety and damage institutional credibility. Psychometric testing is used as a preventive measure to assess the mental and emotional readiness of officers authorized to carry firearms. This article aims to evaluate the implementation of psychometric tests at the Professional and Security Division (Propam) of Palembang City Police as an effort to prevent firearm misuse. This study uses a descriptive qualitative method through observation, documentation, and literature review. Findings show that the implementation of the test remains administrative in nature and is not fully utilized for psychological monitoring or intervention. In conclusion, psychometric testing needs to be strengthened to function effectively as an early detection tool in the internal supervision of the police force.